2021
DOI: 10.1007/s10964-021-01518-9
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Links of Individual and Collective Morality with Adolescents’ Peer Aggression

Abstract: Adolescents’ aggressive behavior has been often linked to biases in morality. However, limited knowledge is available regarding the relative strength of different moral correlates, both at the individual and class-level, in predicting different types of aggressive behavior over time. To address this gap, the present study tested the prospective associations of moral identity and moral disengagement with reactive and proactive aggression in a short-term longitudinal study. The sample consisted of 1158 Italian a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 74 publications
2
13
0
Order By: Relevance
“…The first result suggests that, in classrooms where students more commonly perceive that classmates justify peer aggression in different ways, bullying is more common. This is a salient result that supports the emerging theorizing of moral disengagement as not merely an intrapsychic phenomenon, but also a phenomenon that occurs across individuals within groups (see Gini et al, 2015Gini et al, , 2021. Additionally, our results support the hypothesis that students were more prone to bully others in classrooms where classmates more commonly reported that they assisted and reinforced bullying, a finding that is coherent with earlier studies (Nocentini et al, 2013;.…”
Section: Individual Moral Disengagement and Bullying Among Swedish Fifth Graders: The Role Of Collective Moral Disengagement And Pro-bullsupporting
confidence: 90%
See 4 more Smart Citations
“…The first result suggests that, in classrooms where students more commonly perceive that classmates justify peer aggression in different ways, bullying is more common. This is a salient result that supports the emerging theorizing of moral disengagement as not merely an intrapsychic phenomenon, but also a phenomenon that occurs across individuals within groups (see Gini et al, 2015Gini et al, , 2021. Additionally, our results support the hypothesis that students were more prone to bully others in classrooms where classmates more commonly reported that they assisted and reinforced bullying, a finding that is coherent with earlier studies (Nocentini et al, 2013;.…”
Section: Individual Moral Disengagement and Bullying Among Swedish Fifth Graders: The Role Of Collective Moral Disengagement And Pro-bullsupporting
confidence: 90%
“…The focus in this thesis is on bullying perpetration, although it should be noted that I do not classify the participants as "bullies," but have examined the level of bullying perpetration measured as a quantitative variable. This allowed for a more nuanced and dynamic understanding of bullying involvement (Demaray et al, 2021;Gini et al, 2021). Furthermore, all four studies examined bullying among early adolescents (age span 10-14) and focused on the school context and bullying among students.…”
Section: Defining Bullyingmentioning
confidence: 99%
See 3 more Smart Citations